He Rāngai Maomao, He Iti Pioke: Te Mauri o Pūheke - Maclean, Hohepa (Te Kaharoa, 2012)
This presentation looks at some of the main pillars of language revitalisation suggested by Fishman et al, and how they can be transposed on to an indigenous platform. With Critical Language Awareness, Status Planning, Acquisition Planning and Implementation being the main pillars; the paper explores how these can be translated in to a Māori model.As a reference point, I will look at my own two tribes from the northern part of New Zealand. Patukoraha and Te Whanau Moana, who have experienced severe language loss as evidenced by the depleting numbers of speakers of the reo in contexts such as marae, local meeting house, home, community events etc. A language revitalisation strategy is explored as a way to support these hapū to reverse language shift and the decline of competent speakers and return the language to its appropriate and rightful place in the cultural and social place as the essence of Māoritanga, and integral component of cultural identity.Using both the pillars and Mātāpono Māori, Māori principles of Rangatiratanga, ownership, Whanaungatanga, kinship ties, Kaitiakitanga, guardianship, and Rāhu/Takwai, reservations, and with a base grounded in Whakapapa, genealogical ties, the symbolic nature of a Wheke, octopus (a local guardian totem) was drawn forth. With each arm representing a particular facet, this symbolism, exposes the fundamental aspect that each arm moves independently, but ultimately all ensure the survival of the octopus, relating to the proverb: “one hand washes the other, both wash the face”.